Synthesis and Characterization of a New U.V. Absorber for Low Density Polyethylene - Niema, Salah A. (Basrah Journal for Engineering Sciences, 2015)
A new photostabiliser, U.V. absorber 2, 4 – bis (4- ethylbenzoyl) resorcinol was prepared and characterized by different techniques such as spectroscopic method, elemental analysis, and moleculer weight determination. The absorber was examined for low-density polyethylene and compared with commercial U.V. absorber (Seesorb-100). The new photostabiliser, U.V. absorber showed higher ability to absorb U.V. light and more efficient for photostabilisation for low- density polyethylene, i.e, the optical properties were improved by using this photostabiliser.